Integrated Security Home Automation Based on IOT - V.Srikanth, Prof.; Suchetha, H; Pravllika, K (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT)is the network of home appliances, vehicles and physical devices, which enables the objects to connect and exchange of the data. By using these components IoT supports to develop numerous services in various domains, such as smart cities and smart homes.These components can interact with other components by enabling security such asproxies, data collection, data sharing and other activities in the context of service providence. Until now various research works have studied on these securityissues ofIoT by validating their claim.In this study we are developing a framework, which provides security to the home as well as to operate the appliances in the home using smart technology.For entering into the house using a biometric system, which uses authentication and digital signature to access.We have used biometric system to overcome problems we are facing. In this project there are different sensors such as water level sensor, light sensor, temperature sensor, gas sensor for operation of different appliances in the house.
Keywords: Smart home; Android; SIM; Sensor technology.